2012
DOI: 10.1016/j.jacc.2011.08.061
|View full text |Cite
|
Sign up to set email alerts
|

A Common β1-Adrenergic Receptor Polymorphism Predicts Favorable Response to Rate-Control Therapy in Atrial Fibrillation

Abstract: Background Randomized studies have shown that ventricular rate-control is an acceptable treatment strategy in patients with atrial fibrillation (AF). However, identification of patients who will adequately respond to rate control therapy remains a challenge. Objectives In this study, we evaluated the impact of two common β1-adrenergic receptor (β1-ADR) polymorphisms (G389R and S49G) on response to ventricular rate control therapy in patients with AF. Methods We studied 543 subjects (63% men; age 61.8 ± 14)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 28 publications
3
67
0
7
Order By: Relevance
“…A study by Nia et al demonstrated that the conversion rate of AF with flecainide was highest in patients with the Arg/Arg genotype and lower in glycine carriers. 73 Patients who were glycine carriers did, however, have lower heart rates during AF, corroborating the findings by Parvez et al 77 B 1 AR polymorphisms may alter the efficacy of flecainide because adrenoceptor stimulation induces sodium channel inhibition; 73 therefore, the enhanced adrenergic signaling associated with the Arg/Arg polymorphism may synergistically inhibit sodium channels with flecainide. This adrenergic influence on sodium channels might also explain why the ACT I trial found that patients who had their AF successfully cardioverted with the sodium channel blocker vernakalant had a higher baseline heart rate, which is associated with the Arg/Arg polymorphism.…”
Section: Pharmacogeneticssupporting
confidence: 74%
See 1 more Smart Citation
“…A study by Nia et al demonstrated that the conversion rate of AF with flecainide was highest in patients with the Arg/Arg genotype and lower in glycine carriers. 73 Patients who were glycine carriers did, however, have lower heart rates during AF, corroborating the findings by Parvez et al 77 B 1 AR polymorphisms may alter the efficacy of flecainide because adrenoceptor stimulation induces sodium channel inhibition; 73 therefore, the enhanced adrenergic signaling associated with the Arg/Arg polymorphism may synergistically inhibit sodium channels with flecainide. This adrenergic influence on sodium channels might also explain why the ACT I trial found that patients who had their AF successfully cardioverted with the sodium channel blocker vernakalant had a higher baseline heart rate, which is associated with the Arg/Arg polymorphism.…”
Section: Pharmacogeneticssupporting
confidence: 74%
“…Interestingly, a study by Parvez et al 77 demonstrated that the loss of function glycine 389 polymorphism is associated with a significantly better response to rate-controlling therapies in patients with AF. This may be explained because the rate-control therapies can work synergistically with the attenuated β 1 -adrenergic cascade caused by this genotype.…”
Section: Pharmacogeneticsmentioning
confidence: 99%
“…Several small studies have revealed positive results with the C allele corresponding to an improved response to beta-blockade as defined by reduction in BP or heart failure endpoints [47][48][49][50][51] . Studies have also illustrated contradictory results where the G allele is associated with more favorable rate control with verapamil and multiple beta-blockers 52 .…”
Section: Candidate Pharmacodynamic Polymorphisms Of Adrenergic Responsementioning
confidence: 99%
“…Interestingly, the loss of function glycine 389 polymorphism is associated with a significantly better response to rate-controlling therapies in patients with AF. (43) This may be explained because the rate-control therapies can work synergistically with the attenuated β1-adrenergic cascade caused by this genotype. β1-AR polymorphisms could also influence the efficacy of amiodarone because it possesses antiadrenergic effects.…”
Section: Pharmacogeneticsmentioning
confidence: 99%